Inconsistent outcome reporting in large neonatal trials: a systematic review - Webbe,J; Ali,S; Sakonidou,S; Webbe,T; Duffy,J; Brunton,G; Modi,N; Gale,C (Archives of Disease in Childhood. Fetal and Neonatal Edition, 2019)
ObjectiveInconsistent outcome selection and reporting in clinical trials are important sources of research waste; it is not known how common this problem is in neonatal trials. Our objective was to determine whether large clinical trials involving infants receiving neonatal care report a consistent set of outcomes, how composite outcomes are used and whether parents or former patients were involved in outcome selection.DesignA literature search of CENTRAL, CINAHL, EMBASE and Medline was conducted; randomised trials published between July 1st 2012 and July 1st 2017 and involving at least 100 infants in each arm were included. Outcomes and outcome measures were extracted and categorised by physiological system; reported former patient and parent involvement in outcome selection was extracted.ResultsSeventy six trials involving 43126 infants were identified; 216 different outcomes with 889 different outcome measures were reported. Outcome reporting covered all physiological systems but was variable between individual trials: only 67/76 (88%) of trials reported survival and 639 outcome measures were only reported in a single trial. Thirty three composite outcomes were used in 41 trials. No trials reported former patient or parent involvement in outcome selection.ConclusionsInconsistent outcome reporting and a lack of parent and former patient involvement in outcome selection in neonatal clinical trials limits the ability of such trials to answer clinically meaningful questions. Developing and implementing a core outcome set for future neonatal trials, with input from all stakeholders, should address these issues.